Conservative management in a case of retained adherent placenta in a primigravida patient - Vaidya, Annal Abhay; Panchbudhe, Shruti; Satia, Meena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Morbidly adherent placenta is a serious and a catastrophic pregnancy complication. In this condition, the placenta penetrates deeply inside the uterine walls and is not separated after delivery of the baby. Reporting herewith a case of a primigravida who had undergone Emergency lower segment Caesarean section at a private hospital for severe pregnancy induced hypertension with IUGR and then was referred to Tertiary Care hospital with placenta left in-situ due to non-separation of the placenta at the time of caesarean section. Conservative management was given using Methotrexate which is an anti-metabolite alternatively with Leucovorin (Folinic acid) and followed up with serial ultrasonography with Doppler for placental size and volume and beta-HCG levels which showed a decreasing trend respectively.